Effects of dietary zinc oxide and chlortetracycline on nursery pig growth performance - Julie Ann Feldpausch; Jon A DeJong; Michael D Tokach; Steven S Dritz; Jason C Woodworth; Harvey M Scott; Jim L Nelssen; Robert D Goodband; Raghavendra G Amachawadi (Kansas Agricultural Experiment Station Research Reports, 2014)
A total of 240 weaned pigs (PIC 1050; initially 13.4 lb) were used in a 47-d study to compare the effects of added Zn from zinc oxide (ZnO), alone or in combination with a low or high dose of chlortetracycline (CTC), on nursery pig performance. Pigs were allotted to pens at weaning (d 0) and fed a common starter diet with no antimicrobial for 5 d before the start of the experiment. On d 5, pens of 5 pigs were allotted to 1 of 6 dietary treatments in a randomized complete block design with 8 replications per treatment. Dietary treatments were arranged in a 2 × 3 factorial with main effects of added ZnO (0 vs. 2,500 ppm of Zn) and CTC (0, 50, or 400 g/ton). Pigs were fed experimental diets from d 5 to 26 after weaning followed by a common corn-soybean meal—based diet without antimicrobial from d 26 to 47. Pigs on the 50 g/ton treatment received CTC continuously from d 5 to 26; however, to comply with FDA guidelines, CTC was removed on d 15 from the diets of pigs fed 400 g/ton CTC, then added again from d 16 to 26. All diets contained 110 ppm of Zn from ZnO in the trace mineral premix. No ZnO × CTC interactions were observed. Pigs fed added ZnO had increased (P = 0.001) ADG, ADFI, and ending BW during the treatment period but increased F/G (P = 0.03) from d 26 to 47 when a common diet was fed. Pigs fed CTC had increased (linear, P<0.05) ADG, ADFI, and ending BW during the treatment period as well as a tendency (quadratic, P = 0.08) for improved F/G. Overall (d 5 to 47), pigs fed added ZnO had increased (P<0.05) ADG and ADFI. Overall, pigs fed CTC tended to have increased (linear, P = 0.06) ADG and ADFI, but F/G tended (quadratic, P = 0.07) to decrease then increase as CTC increased. In summary, when ZnO or CTC were added to the diets, increased ADG and ADFI were observed, but additional carryover benefits were not evident after these feed additives were removed from the diets. The benefits of added Zn from ZnO and CTC are additive and could be included together in diets to get the maximum benefit in growth performance of weaned pigs.; Swine Day, Manhattan, KS, November 20, 2014
Keywords: Swine Day; 2014; Kansas Agricultural Experiment Station contribution; no. 15-155-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1110; Growth; Nursery pig; Chlortetracycline; Zinc